Pengembangan E-Modul Menggunakan Flip PDF Professional pada Materi Fungi Kelas X SMA - Anggi Aprilia; Yudiyanto Yudiyanto; Nasrul Hakim (Journal of Education and Teaching (JET), 2022)
The production of e-modules utilizing Flip PDF Professional on Fungi material is inspired by the use of subpar technology and the usage of printed media in learning (powerpoint). Students struggle to comprehend the information. As a result, the goal of this research is to create an e-module using Flip PDF Professional. The ADDIE development model phases are used in this study to apply the R&D (Research and Development) development approach. Material expert validators deemed the outcomes of e-module product validation utilizing Flip PDF Professional "very viable" with a percentage of 90% and media expert validators with a percentage of 95%. Teachers and students rated the test response of the e-module product generated using Flip PDF Professional as "very good," with 93 percent of teachers responding and 94.4 percent of students responding. This might be construed to mean that the developed e-module media is quite capable of being used as an alternate learning medium in the classroom. Furthermore, electronic learning media has a lot of room for improvement and can assist the population in getting a better education. As a result, establishing a feasible standard for the development and management of electronic learning material, as well as supporting infrastructure, is critical.